Zimbabwe : 2003 Article IV Consultation-Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Zimbabwe. (IMF Staff Country Reports; Country Report, 2003)
The Zimbabwean economy has deteriorated progressively over the past four years. Executive Directors expressed deep concern about this, and stressed the need to implement strong macroeconomic, monetary, fiscal, and structural policies. They urged the Reserve Bank of Zimbabwe to ensure that banks meet all prudential regulations, and are adequately capitalized. They welcomed Zimbabwe's participation in the General Data Dissemination Standards, and urged the authorities to strengthen the country's data base to improve the analytical basis for economic policy formulation and IMF surveillance.